The relationship between the characteristics of Generation Z and the implications of the implementation of the 21st century learning skills - Efendi, Efendi; Anwar, Syafri (Universitas Jambi, Indonesia, 2025)
This research used a combined approach of quantitative and qualitative analysis to examine the relationship between the characteristics of Generation Z and the implications of implementing the 21st century learning skills. Participants were members of Generation Z who were involved in surveys and interviews. Quantitative data were analyzed using descriptive statistics and a partial correlation test, while qualitative data were analyzed through a thematic approach. The results showed a significant relationship between the characteristics of Generation Z and the implications of implementing 21st century learning skills. The relationship is evidenced by the partial correlation coefficient of 0.615 (61.5%) with probability (P = 0.002). This explains that Generation Z characteristics, such as learning preferences, learning styles, and understanding of 21st century skills, are interrelated and have an impact on how they interact with learning.